Lithostratigraphy of the Siwalik Group from the Arjun Khola section, Dang district, Mid-western Nepal (Journal of Nepal Geological Society, 2024)
The fluvial sedimentary succession of the Siwalik Group is well exposed along the Inner Churia Range, bounded by the Deukhuri Dun valley to the south and the Dang Dun valley to the north, in the Arjun Khola section, mid-western Nepal. The lithostratigraphy of the succession is divided into the mudstone dominated Lower Siwalik, the sandstone dominated Middle Siwalik and the conglomerate dominated Upper Siwalik based on the lithological variation between mudstone and sandstone, grain size, texture and the distribution of the Siwalik sediments in three belts, which separated by the Central Churia Thrust (CCT) and the Arjun Khola Thrust (AKT) along the section. The magnetostratigraphic data and lithological characters are correlated with the measured thickness, indicate the Lower Siwalik was deposited between 12.5 and 10.98 Ma in the central belt and 12.83-11.5 Ma in the northern belts. Similarly, the Middle Siwalik of central and northern belts were deposited in 10.98-8.36 Ma and 11.5-8.9 Ma respectively. The lithological variation of the study area with other parts of the Siwalik sediments indicates that the study area was deposited in a small river system and represent an interfluve setting of a major river system.